Arthroscopic Resection for Benign Fibrous Histiocytoma in the Epiphysis of the Femur - Junya Shimizu; Makoto Emori; Yohei Okada; Tadashi Hasegawa; Toshihiko Yamashita (Case Reports in Orthopedics)
A 16-year-old woman presented to her local hospital with a few-month history of right knee pain. On MRI, the lesion exhibited an intermediate signal on T1-weighted and T2-weighted images. The orthopedic physician made a diagnosis of osteochondritis dissecans. After 13 months from the first visit, the patient underwent MRI of the knee once more, which demonstrated that the osteolytic lesion grew larger. To achieve a definitive diagnosis, we attempted to perform a resection biopsy with knee arthroscopy. We performed biopsy, and the tumor was removed completely. The tumor occurred in an epiphysis, and the pathological findings concluded that the pathological diagnosis was benign fibrous histiocytoma. One year after surgery, she was asymptomatic. Computed tomography revealed that the previous tumor bone cavity was filled with bone formation and no evidence of recurrence.